Effect of NPR on the flow pattern of circular pipe at high Mach numbers. (2022) - Khan, Sher Afghan; Ridwan; Delvi, Hamza Afser; J. I, Suheel; Attar.M, MashtaqAhamed; Faheem, Mohammed
Abstract: This article aspires to evaluate the effect of dynamic control on the stream's nature in an abruptly expanded conduit of a diameter ratio of 2.2. The investigation was done for Mach 1.6, 1.8, 2.0, and 2.5. Results are shown when control renders any change in the flow field. It is found that at Mach 1.6 for NPR = 7 and the tube size of L = 10D, the jets' noise is considered in the control mechanism's nonappearance and existence. The results show that there is a significant decrease in the noise level, and jets become quiet. It is also observed that the base pressure is also minimal whenever the jet's noise is low due to the microjets. At Mach 1.6, 1.8, and 2.5, the control findings decrease the duct's pressure value for most cases. However, in Mach 2.0, when the control is activated, it increases the duct's static pressure. The microjets do not interrupt the flow field in the pipe adversely.